2007
DOI: 10.1074/jbc.m701603200
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Cystic Fibrosis Transmembrane Conductance Regulator in Mouse Sperm Capacitation

Abstract: Mammalian sperm acquire fertilizing ability in the female tract during a process known as capacitation. In mouse sperm, this process is associated with increases in protein tyrosine phosphorylation, membrane potential hyperpolarization, increase in intracellular pH and Ca 2؉, and hyperactivated motility. The molecular mechanisms involved in these changes are not fully known. Present evidence suggests that in mouse sperm the capacitation-associated membrane hyperpolarization is regulated by a cAMP/protein kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
152
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 96 publications
(169 citation statements)
references
References 52 publications
15
152
2
Order By: Relevance
“…In addition, it is known that Cl À and its channels play important roles in the maintenance of sperm cellular volume [Yeung et al 2004], intracellular pH [Zeng et al 1996], resting membrane potential and excitability [Chan et al 1997;Zhang and Shi 1998]. For example, the sperm cystic fibrosis transmembrane conductance regulator (CFTR) is a cAMP-activated Cl À channel which is involved in the transport of HCO 3 À that is important for sperm capacitation and fertilization [Hernandez-Gonzalez et al 2007;Xu et al 2007]. In addition, Cl À has been reported to be required for the progesterone-, GABA-and zona pellucid-initiated acrosome reaction in mouse, porcine, hamster and human spermatozoa [Espinosa et al 1998;Melendrez and Meizel 1995;Shi et al 1997;Wistrom and Meizel 1993;Yashimatsu and Yanagimachi 1988].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is known that Cl À and its channels play important roles in the maintenance of sperm cellular volume [Yeung et al 2004], intracellular pH [Zeng et al 1996], resting membrane potential and excitability [Chan et al 1997;Zhang and Shi 1998]. For example, the sperm cystic fibrosis transmembrane conductance regulator (CFTR) is a cAMP-activated Cl À channel which is involved in the transport of HCO 3 À that is important for sperm capacitation and fertilization [Hernandez-Gonzalez et al 2007;Xu et al 2007]. In addition, Cl À has been reported to be required for the progesterone-, GABA-and zona pellucid-initiated acrosome reaction in mouse, porcine, hamster and human spermatozoa [Espinosa et al 1998;Melendrez and Meizel 1995;Shi et al 1997;Wistrom and Meizel 1993;Yashimatsu and Yanagimachi 1988].…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this notion, it has been found that fertility in uremic patients may be reduced through alterations in CFTR expression (Xu et al 2012 ). CFTR has been shown to be present in both human and mouse sperm by our group and others, using specifi c antibodies (Chan et al 2006 ;Hernandez-Gonzalez et al 2007 ;Li et al 2010 ;Xu et al 2007 ). Xu et al ( 2007 ) showed, using CFTR inhibitors and specifi c antibodies, as well as heterozygous CFTR mutants, that sperm capacitation and the associated HCO 3 − transport are signifi cantly reduced when compared to mice in normal fertilizing conditions.…”
Section: Cftr Channelsmentioning
confidence: 48%
“…As the sperm resting E m is mildly depolarized (~ −35 mV) and thus shifted from the K + equilibrium potential, it cannot be explained mainly by a high K + permeability through K + channels, as it usually happens in many cells. Just a 10 % contribution of Na + permeability would explain the observed resting E m in noncapacitated sperm, and their inhibition during capacitation would contribute to the observed hyperpolarization (see Hernandez-Gonzalez et al 2006 ;Hernandez-Gonzalez et al 2007 ). CFTR can downregulate ENaCs through mechanisms still not fully understood (Konig et al 2001 ), and the CFTR agonist genistein hyperpolarizes sperm E m (Hernandez-Gonzalez et al 2007 ) and diminishes [Na + ] i (Escoffi er et al 2012 ).…”
Section: Cftr Channelsmentioning
confidence: 99%
See 2 more Smart Citations